UPAYA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA MELALUI METODE SENGKEDAN PADA SISWA KELAS IV SEKOLAH DASAR - Zumaroh, Mimin; Nisa, Ana Fitrotun (Tuladha : Jurnal Pendidikan Dasar, 2023)
Mathematics is a subject that is still considered a scourge and difficult for students to learn. This is due to the factor of inaccurate mathematics learning methods. This problem prompted the author to conduct research using the Swales method in studying FPB and KPK teaching materials. The author conducted a study that aimed to find out whether the use of the Swale method could improve student achievement at SDN Karangrejek I. The type of research used was action research, in which the researcher tried to apply an action as an effort to correct the problems found. The implementation of this research was carried out through 3 cycles. Cycle 1 was held on September 15 and 19 2022, Cycle 2 took place on September 20 2022, and Cycle 3 was held on September 22 2022. The data collected was in the form of results from observations of learning activities, pre-test and post-test scores. The results of the analysis of the score from the pre-test with the results of cycle 1 showed an increase with intervals of 61-80 obtained 55% from 35% previously, then in cycle 2 with intervals of 81-100 obtained 60%, and at the end of the cycle obtained 70%. While students who achieve KKM by going through 3 cycles are as much as 85% or a number of 17 out of 20 students. These results prove that the Swale method can improve student achievement in FPB and KPK teaching materials at SDN Karangrejek I.